Challenges of the Elderly In Zambia. A Systematic Review Study - Masauso Chirwa; Roy Kalinda (European Scientific Journal, ESJ, 2016)
Aging is a phenomenon that is found worldwide. In developed countries, the elderly living conditions are better relative to their counterparts in developing countries. Zambia has a population of slightly over 500,000. A big number of these people reside in rural areas. The aim of this paper was to investigate the challenges experienced by the elderly in Zambia. This was a desk study that used both a quantitative and qualitative methods focusing on the analysis of available literature on aging in Zambia. The results revealed that households with old people are among the poorest in the country. The other challenge faced by the elderly especially in rural areas is social stigma arising from being suspected of practicing witchcraft. They are also left out of the HIV/AIDS statistics and programmes: Currently there seems to be no available HIV/AIDS statistics and programmes for the elderly people aged 65 years and above. Lack of family support and the burden of orphans. Most of the elderly are poor and cannot manage to support their grand children in terms of school, decent shelter, clothing and medical care.